Rokok dan Kejadian Konversi Sputum Pasien Tuberkulosis - Vidi Ibrahim Pratomo Affandi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium Tubrculosa which attacks a person's lungs. Tuberculosis in Indonesia is one of the leading causes of death. One indicator needed to determine the success and evaluation of patients is positive sputum culture containing negative Mycobacterium Tuberculosa bacteria, commonly called sputum conversion. However, several factors and things can cause these indicators of success to fail because patients are still exposed to substances, other diseases that might worsen the condition or failure of treatment. One of them is smoking. The number of cigarette consumption in Indonesia is quite high, so it is a concern for many researchers to review how the influence of smoking on the sputum conversion of TB patients. Cigarettes have active ingredients that can damage the lung's defenses so that TB germs can easily infect a patient's lungs.